The Correlation Between Grammar Mastery and Writing Ability of English Education Department (EED) Studets at Unuversitas Muhammadiyah Yogyakarta (UMY) In Academic Year 2013/2014. - Julisa Arina Haq (PBI 14 UMY 007, 2014)
This study is conducted to know the real data about the correlation between grammar mastery and writing ability of English Education Department at University of Muhammadiyah Yogyakarta in academic year 2013-2014.In this study, the quantitative research was used to analyze the research data. There are two variables of this study which called as independent variable and dependent variable. The independent variable here is grammar mastery and the dependent variable here is writing ability. The population of this study is all students of English Education Department in academic year 2013-2014.The sample of this study is 40 students as representative of whole population. The data of this study is collected in the form of grammar test and writing score. And in the data analysis, this research was used the simple linear regression analysis and Pearson’s r correlation coefficient analysis to describe the correlation between two variables. In the description of the data, the average score of grammar mastery of students is 49.1875. It means the grammar mastery of the students is categorized as medium grammar mastery. Meanwhile, the average score of writing ability of the students is 84.5625. It means the writing ability of the students is categorized as good writing. The pre requirement analysis of this study has been fulfilled. Morever, the hypothesis analysis of this study has been indicated that the correlation coefficient between grammar mastery and writing ability is 0.465, while in Pearson’s r table with the degree 5% and sample of 40 students, the correlation coefficient is 0.312. It can be assumed that the correlation coefficient of 0.465 is significant and it can be used to accept the (Ha) alternative hypothesis because rxy>rt = 0.465>0.312. In other words, the alternative hypothesis can be accepted even the interpretation of this coefficient correlation is categorized as moderate correlation. And the regression equation of Y=72.367+0.248X shows that the increasing and decreasing score of writing ability can be predicted by the score of grammar mastery. Therefore, grammar mastery gives significant contribution to the writing ability. In conclusion, the result of this study is between grammar mastery and writing ability have significant correlation. Therefore, it can be summarized that students of EED students at UMY in academic year 2013-2014 will get high score in writing if they have high score in grammar. In the suggestion of this study,the students of English Education Department at University of Muhammadiyah Yogyakarta in academic year 2013-2014should pay attention to the grammar course and should try to upgrade their grammar mastery in developing their writing ability.